Opening the black box: Developing metrics to assess the cognitive processes of prototyping. (September 2020) - Nelson, Jacob; Menold, Jessica
Abstract : While past work has demonstrated the ability of prototypes to boost design project performance, influence stakeholder buy-in, and improve design team communication, prototyping remains a 'black-box' process. The specific mechanisms through which prototypes affect designer cognition remains unknown. To date, there has been little work to operationalize theory and enable the fine-grain measurement of cognitive processes during prototyping tasks. In short, there is a lack of appropriate metrics to establish the intangible value of prototyping tasks via the measurement of the knowledge generated. The purpose of this work is to propose metrics that more holistically assess the value of prototypes. The proposed metrics are implemented in a design project to validate their utility in studying prototyping tendencies. Highlights: Novel metrics used assess the effect of prototypes on design knowledge across time. Utility of metrics demonstrated to capture fine-grain individual and team data. Results suggest intangible indicators add to our understanding of design cognition.